Production Characteristics of White Karaman, Chios x White Karaman (F1) Crossbred Lambs. II. Fattening Performance, Slaughter and Carcass Characteristics - Esen, Fikret; Yildiz, Nihat (My University, 2000)
This study was carried out to investigate the fattening performance, slaughter and carcass characteristics of White Karaman and Chios x White Karaman (F1) crossbred lambs. The data for the study were obtained from 11 purebred and 12 (6 from each genotype) ram lambs for determination of slaughter and carcass characteristics. Lambs were fed alfalfa hay and concentrates ad libitum in the fattening period. All ram lambs with a live weight of 20 kg were fattened in the same pen until they reached 45 kg live weight and afterwards they were slaughtered for investigation of carcass characteristics. During the fattening period it was determined that average daily live weight gain in purebred and crossbred groups was 245.53 g and 218.87 g, and that the amount of consumed concentrate feeds for 1 kg live weight gain was 3.28 kg and 3.77 kg, respectively. In purebred and crosbred groups slaughtered at 45 kg slaughter weight, the cold carcass weight was 22.10 kg and 21.40 kg, the carcass dressing percentage was 48.88 % and 47.15 %, and the tail fat percentage was 17.85 % and 10.11 %. The difference between the groups for the last parameter was statistically significant (P<0.01).
Akkaraman, Sakiz X Akkaraman Melez (F1) Kuzularda Verim Özellikleri II. Besi Performansi, Kesim ve Karkas Özellikleri
Keywords: Carcass; Chios; Crossbreeding; Fattening; White karaman